Draft Annual Plan 1999-2000 Volume-II Planning Commission Government of India - Planning Commission (Planning Commission, 1999)
Outlay, Physical Target & Achievement General Areas, Hill Areas Summary Statement Externally Aided Project District Planning Centrally Sponsored Schemes Basic Minimum Services TSP SCCP.
Planning Commission Government of India
Planning Commission Government of India